Communicative freedom in a digital democracy: political and economic resistance to freedom of speech and the rise of digital activism in South Africa - Brevis, Chad (Centre for Film and Media Studies, 2022)
This dissertation explores political and economic resistance to communicative freedom in South Africa. Through a mixed methodology of Critical Discourse Analysis and Corpus Linguistics analysis, this dissertation seeks to explore how our understanding of democracy is being transformed as we move from a physical, industrialised world into a digital, networked society. South Africa is trying to keep pace with technological advances while still clinging to archaic forms of governance. This project considers whether these archaic forms of governance and older forms of communication legislation are effective in governing communicative freedom in South Africa's emerging network society. I argue that the Protection of State Information Bill (2010), Protection of Personal Information Bill (2009) and the Promotion of Access to Information Act (2013) are ineffective for two reasons. Firstly, the legislation's language is so open-ended that it can be abused by political and economic elites to stifle free speech and transparency. Secondly, the legislation can be used to punish whistleblowers and digital activists who are vested in sustaining a digital commons in the interest of openness and transparency in a functional democracy. In fact, digital activists say that they experience political and economic intimidation that forces them to self-censor under the threat of heavy-handed sanctions. The problem of corporate monopolisation contributes to this problem because the costs of meaningful online access and participation are prohibitively expensive. Effectively, this undermines constitutionally enshrined communicative freedoms. I also explore historical and theoretical approaches to democracy and consider what democracy is in a developing network society. This leads to a discussion of the ways in which vague language choices within laws are used to subvert and undermine the right to communicative freedom. I then engage the work of the civil society organisation, the Right2Know Campaign (R2K), as a legitimate response to impunitive exercises of power. The dissertation offers a Corpus Linguistics analysis of the Protection of State Information Bill (2010), Protection of Personal Information Bill (2009) and the Promotion of Access to Information Act (2013) to suggest that, in the nexus between political and economic resistance to communicative freedom and digital activism, South Africa has regressed into an autocratic dystopia. The argument is that digital activism should be protected in the same way as physical protests in our material world. In an age where South Africa's socio-political and economic sectors are reimagined in the digital space, an inevitable reliance on digital activism has emerged. This study explores newer forms of governance that may be established in the power vacuum created in the new, digital space of politics and economics in our networked society.